Greece Faces a Yin-Yang Development Phase - Stefania Andra Simionescu (CES Working Papers, 2015)
The concept Yin-Yang represents the unity of opposites and complementarity. In this respect, from the economical point of view a positive Yin phase represents the cash flow, brings nutrition, gentleness and protection, while a negative Yin phase means capital loss, sloth and passive obedience; a positive Yang phase is translated as an action based on funds, emphasising the creation, the construction and the development of infrastructure thanks to an economical action plan, while a negative Yang phase leads to conflicts, to excessive product stocks and to a stock market collapse, causing, in this line, crisis and inflation by increasing prices and decreasing purchasing power. In the European Union, Greece faces a Yang negative phase. When having too much positive Yin monetary stimulus from the EU, the Yin-Yang balance turns in favour of a negative Yang bankrupcy and unemployment. Thus, I explore not only the Greece's economical dimension, but also its geographic role, the synergy between culture and DNA and the last, but not the least, the human's ability in creating a new positive Yin-Yang flourishing future.
Keywords: I30; N40; 330; Greece; the European Union; Yin-Yang; development; gravitation